Clomiphene Citrate Treatment as an Alternative Therapeutic Approach for Male Hypogonadism: Mechanisms and Clinical Implications - Yao-Cheng Wu; Wen-Wei Sung (MDPI AG, 2024)
Male hypogonadism, which is characterized by low testosterone levels, has a significant impact on male sexual function, overall health, and fertility. Testosterone replacement therapy (TRT) is the conventional treatment for this condition, but it has potential adverse effects and is not suitable for men seeking to conceive. Testosterone plays an essential role in male sexual function, metabolism, mood, and overall well-being. Clomiphene citrate, a drug originally developed for female infertility, has recently gained attention as an off-label treatment for male hypogonadism. By blocking the negative feedback of estrogen on the hypothalamus and pituitary glands, clomiphene stimulates gonadotropin secretion, leading to increased endogenous testosterone production, which, in turn, improves sperm parameters and fertility and alleviates the symptoms of hypogonadism. Regarding the safety profile of clomiphene compared with TRT, clomiphene appears to confer a lower risk than TRT, which is associated with adverse effects such as polycythemia. Furthermore, combination therapy with clomiphene and anastrozole or human chorionic gonadotropin has been investigated as a potential approach to enhancing the effectiveness of treatments for improving hypogonadism symptoms. In conclusion, clomiphene citrate may offer a promising alternative to TRT for men with hypogonadism, particularly those desiring fertility preservations. However, its long-term efficacy and safety remain inadequately understood. Future research should focus on exploring the benefits of combination therapies and personalized treatment strategies based on individual patient characteristics.